Nautical Eco-Lexicon of Lamaholot Language of Bahinga Village - Fransiska Jone Mare (RETORIKA: Jurnal Ilmu Bahasa, 2018)
This study examines the treasury of eco-lexicon in order to reveal the level of society's knowledge on the diversity of lexicon, the metaphorical expressions and the mythology of the nautical matter of the language. To achieve these objectives, I made use of quantitative-qualitative research method. I collected the data by using observation, interview and questionnaire methods. The results of the study show there are 87 nautical nominal laxicons in the form of base, 24 lexicons in the form of phrase, and 16 lexicons in the form of verb "to catch"; there are 18 lexicons connecting to the expression of metaphors and myths of nautical matter that are dilated by the three dimensions of social praxis; and the level of society’s knowledge about the lexicon, metaphorical expressions, and myth of nautical matter of Lamaholot language in Bahinga Village is among others: the group of elderly have an average knowledge of 76% and above (really know), adults have an average knowledge of 51% 75% (know), and adolescents have an average knowledge of 26% -50% (less know).